O impacto do aumento das alíquotas sobre transmissão à título gratuito inter vivos (doação) na arrecadação do ITCMD do Estado do Ceará - Teixeira, Maria Darlene Lopes (2020)
In 2015, the State of Ceará, in line with the national trend, instituted, through Law 15812/2015, an increase in the progressive rates of on free inter stream transmission charged from 2% and 4% to 2 %, 4%, 6%, and 8%, equating them with the rates on transmission cause Mortis. The objective of this work is to examine whether, with the change in the rates, there was an increase in the collection of ITCMD, especially in the second half of 2015, the period before the law came into effect (Principle of Priority in conjunction with the Principle of Noventena), thus certifying whether this initiative effectively contributed to the increase in the ITCMD in the State of Ceará. To carry out this study, Structural Breakdown Tests were prepared in the ITCMD collection series, which are ITCD, Active Debt and Installments, referring to the period from January 2005 to November 2019, provided by the State Finance Department of Ceará. It was found that there was only evidence of changes in the installment structure of the installment, which showed a significant break in a confidence interval between May to November of 2015. This means that between the dates on which the law was enacted and in force, respectively, July 20, 2015, and January 1, 2016, there was an increase in tax collection, indicating that the taxpayer decided to transfer the goods before the law came into force, thus avoiding the payment of the tax with higher rates.